Pengaruh Pengeluaran Kesehatan, Dana Perimbangan, Dan Penduduk Miskin Terhadap Indeks Pembangunan Manusia Di Provinsi Papua Barat - Fakhri Abdillah; M.Sri Wahyudi (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the influence of goverment spending on education, balancing fund and the number of poor people on human development index (HDI). The data used in this study is secondary data for the period 2014-2019. human development index (HDI) as dependent variable, while goverment spending on education, balancing fund and the number of poor as Independent variables. The research method used is the analysis of the regression of panel data. The analysis tool uses Eviews9 which includes Chow test, Hausman test, normality test, multicollinearity test, heteroscedaticity. The results of this study are goverment spending on education has a positive and significant effect on human development index (HDI), balancing fund has a positive and significant effect on human development index (HDI), and the number of poor people has a negative and significant effect on human development index (HDI).